2014
DOI: 10.2139/ssrn.2487741
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Community-Based Sponsorship Impact on Self-Congruity

Abstract: Determinants of community-based sponsorship impact on self-congruity Psychology & Marketing, 2013; 30(11) Publishing in a subscription based journal Accepted (peer-reviewed) VersionSelf-archiving of the accepted version is subject to an embargo period of 12-24 months. The embargo period is 12 months for scientific, technical, and medical (STM) journals and 24 months for social science and humanities (SSH) journals following publication of the final article.The accepted version may be placed on:• the author's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Yet, the sponsorship of sport has received little academic attention in the CSR domain (Peloza and Shang, 2011). While some initial research has suggested the ability of sport sponsorship to build sponsor CSR image (i.e., Quester et al, 2013), empirical investigations of whether sport sponsorship can facilitate the development of CSR image are lacking. As a result, no guidance exists regarding the type of sport property that is most conducive to a socially responsible image for the sponsor.…”
Section: Sport Sponsorship and Corporate Social Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the sponsorship of sport has received little academic attention in the CSR domain (Peloza and Shang, 2011). While some initial research has suggested the ability of sport sponsorship to build sponsor CSR image (i.e., Quester et al, 2013), empirical investigations of whether sport sponsorship can facilitate the development of CSR image are lacking. As a result, no guidance exists regarding the type of sport property that is most conducive to a socially responsible image for the sponsor.…”
Section: Sport Sponsorship and Corporate Social Responsibilitymentioning
confidence: 99%
“…Indeed, sponsoring professional sport organizations is unlikely to lead to an improved CSR image for the sponsor, unless the sport organization develops its own image as a caring and engaged corporate citizen (Quester et al, 2013). However, the same added benefits are unlikely to arise for sponsors of grassroots properties.…”
Section: Corporate Social Responsibility Imagementioning
confidence: 99%
See 1 more Smart Citation
“…That is, sponsorship is more of "an investment, in cash or in-kind, in an activity, in return for access to the exploitable commercial potential associated with that property" [27] (p. 36). Sponsorship typically involves the following three agents: a sponsor, property, and consumers [28]. The property receives a payment, and the sponsor obtains the right to associate with the property [29].…”
Section: Socially Responsible Corporate Activitiesmentioning
confidence: 99%
“…Brands affiliated with firms that actively engage in CSR activities are perceived as moral brands, and this perception contributes to a favorable evaluation of the brands (Choi & Winterich, 2013;Collins, Steg, & Koning, 2007;Maignan & Ferrell, 1999;Sen & Bhattacharya, 2001). Moral benefits may involve the company's contribution to the local community (e.g., Carroll, 1999;Kourovskaia & Meenaghan, 2013;Quester, Plewa, Palmer, & Mazodier, 2013), whether the company treats its employees fairly (e.g., Sen & Bhattacharya, 2001), whether the company is a good environmental steward (e.g., Drumwright, 1994;Menon & Menon, 1997;Mostafa, 2007;Pagiaslis & Krontalis, 2014), and whether it contributes to worthwhile charities and treats its customers with care (e.g., Smith & Cooper-Martin, 1997). Thus, consumers' moral evaluation of the company affiliated with a brand is likely to influence their postconsumption evaluations (e.g., Bhattacharya & Sen, 2003;Choi & Winterich 2013;Marin & Ruiz, 2006;Paul et al, 2009).…”
Section: Conceptual Developmentmentioning
confidence: 99%